Effects of uniconazole treatment on ‘Hass’ avocado productivity and gas-exchange parameters under Mediterranean climate - Lahack, Michal; Szenes, Nitzan; Rubinovich, Lior (Frontiers in Plant Science, 2025)
Avocado (Persea americana Mill.) productivity faces major challenges due to rising market demand, climate variability, excessive vegetative growth, and labor-intensive management practices. This study evaluated the effects of soil-applied uniconazole (UNI), a gibberellin-biosynthesis inhibitor, on vegetative development, flowering, gas exchange, and fruit yield in mature ‘Hass’ avocado trees. The experiment, conducted over 2 years in a commercial orchard in northeastern Israel, compared three UNI concentrations (8, 12, and 16 mL tree-¹) applied via drip irrigation in May 2022 and May 2024. UNI treatments significantly reduced trunk diameter and increased floral bud density, indicating effective suppression of growth. Flowering intensity was enhanced during the first season across all UNI treatments, but not in the following year. Chlorophyll content showed a significant increase only in May 2023 for the 12 and 16 mL tree-¹ treatments. Physiological measurements revealed increased carbon assimilation and stomatal conductance in UNI-treated trees, particularly during the first season. Despite reductions in total yield at higher UNI doses in the first year of the experiment, the 12 and 16 mL tree-¹ treatments produced significantly larger fruit with improved size-class distribution, offering potential market advantages. Overall, the 8 mL tree-¹ treatment provided the best compromise between suppressing vegetative growth and enhancing carbon assimilation without compromising yield. These findings underscore the potential of UNI for optimizing canopy architecture and fruit quality in avocado orchards, particularly under a Mediterranean climate. Long-term assessments are recommended to refine dose strategies and evaluate commercial viability.